Monitoring the Climate Impact of Fiscal Policy : Lessons from Tracking the COVID-19 Response - Eltokhy, Khaled (IMF Working Papers; Working Paper ;, 2021)
In the wake of the COVID-19 crisis, governments around the world announced unprecedented fiscal packages to address the economic impact of the crisis. The unusually large scale of the packages was accompanied by widespread calls for "greening" them to meet the dual goals of economic recovery and environmental sustainability. In response, several researchers and international organizations attempted to assess the "greenness" of the fiscal policy response of the world's largest economies. This paper takes stock of the contributions made by these various trackers, identifies strengths and weaknesses of their methodologies, and draws lessons for assessing the climate impact of fiscal policy going forward. It finds that: trackers provided useful assessments of the (generally low) level of greenness and raised awareness; trackers' methodologies, while valid and innovative, varied significantly with some important, if currently largely unavoidable, weaknesses; and the way forward should involve tracking the greenness of entire government budgets, rather than just their response to the COVID-19 crisis.